The Network Governance of Crisis Response: Case Studies of Incident Command Systems - Moynihan, Donald P. (My University, 2008)
This examination of hierarchical incident command systems (ICS) used in crises explores how the network properties of crisis responses fundamentally affect ICS operations in terms of coordination, authority and trust.